USING INTERNATIONAL PHONETIC ALPHABET (IPA) IN TEACHING PRONUNCIATION: LINGUISTICS IN PRESENT CENTURY - Mas Sulis Setiyono (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
The aims of this research are to describe the use of International Phonetic Transcription (IPA) in teaching pronunciation. IPA (International Phonetic Alphabet), which was established in 1886 by a group of European phoneticians, is used as the standard of doing phonemic transcript. The term ‘Phonetic Transcription’ in this research refers to the set of symbols used to characterize the set of distinctive sounds of English. The subjects of the research were one lecturer of pronunciation subject and 39 students of the first semester at English Department Veteran Bangun Nusantara University Sukoharjo in 2017/ 2018 academic year. The researcher collected data by using interview, observation, questionnaire, and documentation. All data of the research was taken during teaching and learning process in pronunciation class. The result of the study showed that the use of IPA by combining it using various teaching method can help the students in learning pronunciation. Lecturer and most of the students think that IPA is needed and very beneficial in learning pronunciation.